SIFAT KIMIA TIGA JENIS KAYU RAKYAT - Yuniarti Yuniarti (Kementerian Perindustrian, 2011)
The objective of this study was to determine the chemical components of three kinds of social forestry timber of Jengkol, Madang, and Bangkinang, where wood samples was procured from Loksado South Kalimantan. The analysis was conducted according to TAPPI Standard with three replications for each sample. Result shows that Jengkol wood contained 44.73% of cellulose, 79.19% of holocellulose, 32.14% of lignin, 4.08% of extractive and 3.42% of ash. Madang wood contained 45.02% of cellulose, 80.05% of holocellulose, 31.60% of lignin, 4.06% of extractive and 4.59% of ash. Bangkinang wood contained 45.76% of cellulose, 72.84% of holocellulose, 20.90% of lignin, 2.89% of extractive and 3.9% of ash. This research indicated that among three social forestry timber investigated, the Bangkinang wood is better than two others as sources of raw material for pulp and paper due to the highest cellulose content and lowest lignin and extractives contents.Keywords: chemical properties, Jengkol, Madang, Bangkinang